2011
DOI: 10.1590/s0100-69162011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Estudos sobre a mensuração da condutividade elétrica do solo

Abstract: RESUMO:A condutividade elétrica é a capacidade que um material possui em conduzir corrente elétrica, e uma das suas utilidades na agricultura provém do fato de que a massa do solo com sua variabilidade na composição físico-química apresenta diferentes níveis de condutividade elétrica (CE). O objetivo do presente trabalho foi estudar o comportamento da CE no solo e avançar no entendimento dos fatores que regem seus níveis de variação e desenvolver sistemas que permitam a mensuração contínua da CE do solo para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
2
14
0
6
Order By: Relevance
“…Também possível verificar correlação positiva entre CEa medida de 0-0,3 m com a saturação por bases, K trocável, soma de bases trocáveis e Ca trocável, de (valor de r) 0,56, 0,48, 0,48 e 0,46, respectivamente. Pelas relações estabelecidas a condutividade elétrica pode ser uma boa ferramenta para identificar a variabilidade de acidez e fertilidade no solo (Molin & Rabello, 2011;Zonta et al,2014).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Também possível verificar correlação positiva entre CEa medida de 0-0,3 m com a saturação por bases, K trocável, soma de bases trocáveis e Ca trocável, de (valor de r) 0,56, 0,48, 0,48 e 0,46, respectivamente. Pelas relações estabelecidas a condutividade elétrica pode ser uma boa ferramenta para identificar a variabilidade de acidez e fertilidade no solo (Molin & Rabello, 2011;Zonta et al,2014).…”
Section: Resultsunclassified
“…A CEa também tem relação com os atributos físicos, como umidade do solo, que é determinada pela textura, estrutura e a matéria orgânica (Molin & Rabello, 2011). A CEa pode ser facilmente obtida no campo a partir de leituras com o sensor Veris 3100 e potencialmente utilizada para delimitar zonas homogêneas.…”
Section: Introductionunclassified
“…It means that, the low-low cluster map for these soil properties can be manage in the same way and the CE20 can be used to identify then. MOLIN & RABELLO (2011), in a detailed study using a commercial measuring equipment of apparent soil electrical conductivity, obtained results that indicated apparent soil electrical conductivity relates with soil texture and MC.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers (CORWIN & LESCH, 2003;LESCH et al, 2005;MORAL, et al, 2010;MOLIN & RABELLO, 2011;SAEY et al, 2009;YAN et al, 2007;YAN et al, 2008) have demonstrated the importance of the electrical soil properties in explaining the variability of the soil's physical and chemical properties and crop yields. The apparent soil electrical conductivity has become one of the most common tools for characterizing the spatial variability of a field because it is reliable and easy to measure (CORWIN & LESCH, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Soil apparent electrical conductivity (ECa) has also been used as an auxiliary parameter in delineating management zones (Kitchen et al, 2005;Li et al, 2007;Valente et al, 2012) because of its strong correlation with different soil properties (Moral et al, 2010;Molin & Rabello, 2011;Kweon et al, 2013). Nevertheless, there are very few studies using ECa to delineate management zones for sandy and sandy loam soils of largely irrigated agricultural areas, such as those in the Submédio São Francisco River Basin, located in the semiarid region of Brazil.…”
Section: Introductionmentioning
confidence: 99%